I have a question about evaluating

$$\int_{0}^{\infty} \frac{1-\cos t}{t} \, e^{-t} \, \mathrm{d} t$$

Since $\lim_{t \to 0} \frac{1-\cos(t)}{t} =0$, we know that the integrand is integrable near $t=0$.

But when evaluating the integral, how do you deal with the $t$ in the denominator of the integrand?

  • $\begingroup$ I hope the method is the simplest:) $\endgroup$ – Paul Jun 5 '14 at 13:21
  • $\begingroup$ The fact that this question is so heavily upvoted is baffling... $\endgroup$ – tomasz Jun 8 '14 at 11:10

Consider $$\mathcal{I}(a)=\int_0^{\infty}\frac{1-\cos at}{t}e^{-t}dt.$$ Differentiating w.r.t. $a$, we find $$\mathcal{I}'(a)=\int_0^{\infty}\sin at\;e^{-t}dt=\frac{a}{1+a^2}.$$ Now integrating back and using that $\mathcal{I}(0)=0$ yields $$\mathcal{I}(a)=\int_0^a\frac{a\,da}{1+a^2}=\frac12\ln\left(1+a^2\right).$$ It remains to set $a=1$.

  • 3
    $\begingroup$ You are too fast! :P I solved it by considering $I(a)=\int_0^{\infty} \frac{1-\cos t}{t}e^{-at}\,dt$ but I think both the approaches are similar so I didn't post it. :D $\endgroup$ – Pranav Arora Jun 5 '14 at 13:37
  • $\begingroup$ @Paul You are welcome! $\endgroup$ – Start wearing purple Jun 5 '14 at 13:47
  • $\begingroup$ Does this method have a name? I haven't seen an integral evaluated this way before. $\endgroup$ – Achal Jun 5 '14 at 20:37
  • $\begingroup$ @Achal Differentiation under the integral sign. Sometimes people also refer to Feynman. $\endgroup$ – Start wearing purple Jun 5 '14 at 21:09
  • $\begingroup$ What is the justification for moving the differentiation into the integral? $\endgroup$ – Brofessor Aug 26 '18 at 7:37

Assume that $a>1$.

Using the Maclaurin series of the cosine function, we get

$$\begin{align} \int_{0}^{\infty} \frac{1-\cos t}{t} \, e^{-at} \, dt &= -\int_{0}^{\infty} \sum_{n=1}^{\infty} \frac{(-1)^{n}t^{2n}}{(2n)!} \frac{e^{-at}}{t} \, dt \\ &= \sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{(2n)!} \int_{0}^{\infty}t^{2n-1}e^{-at} \, dt \\ &=\sum_{n=1}^{\infty}\frac{(-1)^{n+1}}{(2n)!} \frac{(2n-1)!}{a^{2n}} \\ &= \frac{1}{2}\sum_{n=1}^{\infty} \frac{(-1)^{n+1}}{n} \left( \frac{1}{a^{2}} \right)^{n} \\ &=\frac{1}{2} \,\ln \left(1+ \frac{1}{a^{2}} \right) \, , \end{align}$$ where interchanging the order of summation and integration is justified by Fubini's theorem.

Letting $a \to 1^{+}$, we get $$\int_{0}^{\infty} \frac{1-\cos t}{t} \, e^{-t} \, dt = \frac{\ln 2}{2}. $$

(See this question about justification for moving the limit inside the integral.)

  • 2
    $\begingroup$ Brilliant! +1. Never crossed my mind to use this method. I tried to use Frullani's integral but I couldn't. $\endgroup$ – Tunk-Fey Jun 5 '14 at 15:13
  • $\begingroup$ @Tunk-Fey: I have posted a solution using Frullani's integral. :) $\endgroup$ – Pranav Arora Jun 5 '14 at 17:36
  • $\begingroup$ And as always, great solution Random Variable! :) $\endgroup$ – Pranav Arora Jun 5 '14 at 17:37

Consider the integral $$\int_0^\infty \frac{1-\cos t}{t} e^{-st} dt. $$ If we define $f(t)=1-\cos t$, this integral is the Laplace transform of $f(t)/t$. Moreover, we have the following identity for Laplace transforms:

$$\mathcal{L} \left\{ \frac{f(t)}{t} \right\}(s)=\int_s^\infty F(\sigma)d \sigma $$ where $F(\sigma)$ is the Laplace transform of $f(t)$, which in our case is known to be $$F(\sigma)=\frac{1}{\sigma}-\frac{\sigma}{\sigma^2+1}. $$ Thus we have $$\int_0^\infty \frac{1-\cos t}{t} e^{-st}=\int_s^\infty \left( \frac{1}{\sigma}-\frac{\sigma}{\sigma^2+1} \right) d \sigma= \log \sigma-\frac{1}{2} \log (\sigma^2+1) \big]^{\sigma=\infty}_{\sigma=s} .$$ Plugging in $s=1$ gives $$\int_0^\infty \frac{1-\cos t}{t} e^{-t} dt=\frac{1}{2} \log 2- \log 1=\frac{1}{2} \log 2 .$$

  • 1
    $\begingroup$ We have a same approach. I didn't notice your answer because I used my tablet to type the answer. Sorry for that. +1. $\endgroup$ – Tunk-Fey Jun 5 '14 at 14:34

Another approach

Consider Laplace transform $$ \mathcal{L}\left[f(t)\right]=F(s)=\int_0^\infty f(t)\ e^{-st}\ dt $$ and property of the unilateral Laplace transform $$ \mathcal{L}\left[\frac{f(t)}{t}\right]=\int_s^\infty F(\omega)\ d\omega, $$ where $F(\omega)$ is Laplace transform of $f(t)$. We choose $f(t)=(1-\cos at)$ and it is easy to show that $$ \mathcal{L}\left[1-\cos at\right]=F(s)=\int_0^\infty (1-\cos at)\ e^{-st}\ dt=\frac{a^2}{s(s^2+a^2)}, $$ then $$\eqalign { \mathcal{L}\left[\frac{1-\cos at}{t}\right]&=\int_1^\infty \frac{a^2}{s(s^2+a^2)}\ ds\\ &=\int_1^\infty \left[\frac{1}{s}-\frac{s}{s^2+a^2}\right]\ ds\\ &=\left.\frac12\left[\ln s^2-\ln(s^2+a^2)\right]\right|_1^\infty\\ &=\left.\frac12\ln\left(\frac{s^2}{s^2+a^2}\right)\right|_1^\infty\\ &=\frac12\ln\left(1+a^2\right). } $$ Taking $a=1$ yields $$ \int_0^\infty \left[\frac{1-\cos t}{t}\right]\ e^{-t}\ dt=\large\color{blue}{\frac{\ln 2}{2}}. $$


Here's a solution using Frullani's integral.

$$\int_0^{\infty} \frac{1-\cos t}{t}e^{-t}\,dt=\Re\left(\int_0^{\infty} \frac{1-e^{it}}{t}e^{-t}\,dt\right)=\Re\left(\int_0^{\infty} \frac{e^{-t}-e^{-(1-i)t}}{t}\,dt\right)$$ $$=\Re\left(\ln\left(\frac{1-i}{1}\right)\right)=\Re\left(\ln\left(\sqrt{2}e^{i(-\pi/4+2k\pi)}\right)\right)=\boxed{\dfrac{\ln 2}{2}}$$

  • 1
    $\begingroup$ Wait!? I got the result until $\Re[\ln(1-i)]$ but when I used W|A the answer is $1$. I forgot to use the way that you used. Darn! $\endgroup$ – Tunk-Fey Jun 5 '14 at 17:50
  • $\begingroup$ @Tunk-Fey: But still, why does W|A gives 1? Any ideas? :/ $\endgroup$ – Pranav Arora Jun 5 '14 at 17:51
  • $\begingroup$ I don't know!? Have you clicked the link? $\endgroup$ – Tunk-Fey Jun 5 '14 at 17:52
  • $\begingroup$ @Tunk-Fey: Yes, I clicked it and it shows 1 as the answer. $\endgroup$ – Pranav Arora Jun 5 '14 at 17:52
  • $\begingroup$ However, if I enter this: wolframalpha.com/input/… it shows the correct result. $\endgroup$ – Pranav Arora Jun 5 '14 at 17:54

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\int_{0}^{\infty}{1 - \cos\pars{t} \over t} \expo{-t}\,\dd t =\ {\large ?}}$

\begin{align} &\color{#44f}{\large\int_{0}^{\infty}{1 - \cos\pars{t} \over t} \expo{-t}\,\dd t} =\Re\int_{0}^{\infty}\bracks{% \expo{-t} - \expo{-\pars{1 + \ic}t}}\int_{0}^{\infty}\expo{-t\xi}\,\dd\xi\,\dd t \\[3mm]&=\Re\int_{0}^{\infty}\int_{0}^{\infty}\bracks{% \expo{-\pars{1 + \xi}t} - \expo{-\pars{\xi + 1 + \ic}t}}\,\dd t\,\dd\xi =\Re\int_{0}^{\infty}\bracks{{1 \over \xi + 1} - {1 \over \xi + 1 + \ic}}\,\dd\xi \\[3mm]&=\Re\ln\pars{1 + \ic} = \color{#44f}{\large\half\,\ln\pars{2}} \end{align}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.